Common Mechanisms Underlying Opioid Tolerance and Dependence and Neuropathic Pain: Role of Metabotropic Glutamate Receptors - Marian E Fundytus (Pain Research and Management)
It has been suggested that opioid tolerance and dependence share common mechanisms with neuropathic pain. This short review deals with the role of glutamate and glutamate receptors in opioid tolerance and dependence, and neuropathic pain. Particular attention is given to the role of metabotropic glutamate receptors (mGluRs). First, the different types of glutamate receptors, which include N-methyl-D-aspartate, alpha-amino-3-hydroxyl-5-methyl- isoxazole-4-propionic acid, kainate and mGluRs, are described. Following this, evidence suggesting that these receptors are involved in opioid tolerance and dependence are summarized. At the end of this section, a model that has been previously proposed to explain mechanisms by which mGluRs may be involved in opioid tolerance and dependence are described. Next is a discussion of the evidence suggesting that glutamate receptors are similarly involved in neuropathic pain, and also in opioid sensitivity associated with neuropathic pain. Again, a hypothetical model used to explain mechanisms by which mGluRs may be involved in neuropathic pain is briefly described. The relevance of the data is discussed in terms of some of the clinical implications of the material presented in the article.